Contrastive study on porphyrinic iron metal-organic framework supported on various carbon matrices as efficient electrocatalysts - Liu, Jian; Bo, X.; Li, M.; Yin, D.; Guo, L. (Academic Press, 2018)
© 2017 Elsevier Inc. Porphyrinic iron metal-organic framework (pFeMOF) was combined with different kinds of carbon matrices, including porous graphene (PG), ordered mesoporous carbon (OMC) and macroporous carbon (MPC) via a simple one-step hydrothermal method. The introduction of carbon substrates improves the electrical conductivity and stability of pFeMOF. The presence of carbon also reduces the size of pFeMOF crystallites, leading to more active sites. The catalysts were used to electrocatalysis of hydrogen evolution reaction (HER) and the reduction of hydrogen peroxide (H2O2). Electrochemical measurements show that pFeMOF/PG has better electrocatalytic efficiency than pFeMOF/OMC, pFeMOF/MPC and pFeMOF. The HER on pFeMOF/PG displays a small onset potential of -34.37 mV vs. reversible hydrogen electrode (RHE), a low Tafel slope of 73.06 mV dec-1, a small over-potential of 154.71 mV at 10 mA cm-2. The catalytic effect for H2O2is also satisfied. The linearity range of H2O2is as wide as 5–4310 µM, and the sensitivity is as high as 77.38 µA mM-1. Such splendid performances may be attributed to the crumpled structure of PG leading to evenly and smaller pFeMOF. Furthermore, abundant hierarchical pores of pFeMOF/PG result in larger electrochemically surface areas. Our work may provide a new approach to design efficient non-precious metal catalysts.